Pomen divje živečih družin medonosne čebele za gozd in čebelarstvo - Prešern, Janez (Gozdarski vestnik, 2016)
Wild honey bee colonies in forest are important from two viewpoints: the ecological one, where they play an important role as pollinators in the food chain, and as a vector of plant pathogens. The knowledge of wild bee colonies is at least equally interesting from the beekeeping aspect, since the normal natural selection, essential for the adjustment of the honey bee to the newly arrived pathogens, takes place only in Wild honey bee colonies.
Keywords: kranjska čebela; medonosna čebela; gozdovi; čebelarstvo; ecology; ekologija; funkcije gozdov